Motives of Non-Muslim Customers Using Services at PT Bank Syariah Mandiri Sibolga Branch Office - mirna sari; darwis harahap; sry lestari; ferri alfadri (Journal Of Sharia Banking, 2021)
This research was motivated by in addition to Muslim customers it turns out there are also non-Muslim customers who are customers at Bank Syariah Mandiri Sibolga Branch Office. The purpose of this research is to find out whether there are many non-Muslim customers in BSM Sibolga and to find out what the motives of non-Muslim customers are using the services of Bank Syariah Mandiri Sibolga branch office. This type of research is descriptive qualitative. This research takes place in BSM Sibolga with research subjects of Bank employees: customer service, leadership, security guards and 9 non-Muslim customers related to the motives of non-Muslim customer customers in using services at BSM Sibolga, in this study supported by observation, interviews and documentation data. The results of this study conclude that the motives of non-Muslim customers in using BSM Sibolga services include: Personal motives namely work, cultural motives namely geographical (location) and groups (organizations or invitations from neighbors), and religious motives stimuli namely products. The most commonly found motif is a geographical motif, namely the location of Bank Syariah Mandiri Sibolga, located on the side of the road and easy to reach. Not found in the field of religious motives (religious observance), social motives (wealth, power and mastery of knowledge of personal motives (age and lifestyle). Non-Muslim customers Bank Syariah Mandiri Sibolga Branch Offices are mostly interested in gold pawning products. researchers conducted interviews with only a few non-Muslim customers who used gold pawning products that were found.